Rapid Detection of the Aeromonas sp. group using Conventional PCR at the Aquaculture Technology Development Center, Cangkringan, Sleman, Special Region of Yogyakarta - Nurhafid, Mohammad; Astuti; Riady, Reza Muhammad; Ufianah; Pardiyanto, Eko; Ruanda, Faldo Ody (PT. Artha GenetikaLab Indonesia, 2023)
The catfish is a freshwater cultivated fish that can be found all over Indonesia. However, the problems that occur in general are usually attacks by pathogens from the Aeromonas sp group. This research aims to optimize the rapid detection of the Aeromonas sp group using PCR at the Aquaculture Technology Development Center, Cangkringan, Sleman, special region of Yogyakarta. The research was conducted by survey with purposive sampling. Isolation was carried out using two growth media, namely Tryptone Soy Agar (TSA) and Glutamate Starch Phenile (GSP). Colonies that had characteristics of the Aeromonas sp group were subjected to PCR amplification using specific primers for the Aeromonas sp group. The results of the amplification resulted in DNA that matched the target, namely 953bp, which showed that the sample belonged to the Aeromonas sp group. Based on this technique, the level of accuracy in detecting pathogens is higher than conventional methods.